Leaf heteroblasty in Passiflora edulis as revealed by metabolic profiling and expression analyses of the microRNAs miR156 and miR172 - Silva, Priscila O; Batista, DIego S; Cavalcanti, João Henrique F; Koehler, Andréa D; Vieira, Lorena M; Fernandes, Amanda M; Barrera-Rojas, Carlos Hernan [UNESP]; Ribeiro, DImas M; Nogueira, Fabio T. S; Otoni, Wagner C (Oxford University Press (OUP), 2019)
Background and Aims: Juvenile-to-adult phase transition is marked by changes in leaf morphology, mostly due to the temporal development of the shoot apical meristem, a phenomenon known as heteroblasty. Sugars and microRNA-controlled modules are components of the heteroblastic process in Arabidopsis thaliana leaves. However, our understanding about their roles during phase-changing in other species, such as Passiflora edulis, remains limited. Unlike Arabidopsis, P. edulis (a semi-woody perennial climbing vine) undergoes remarkable changes in leaf morphology throughout juvenile-to-adult transition. Nonetheless, the underlying molecular mechanisms are unknown. Methods: Here we evaluated the molecular mechanisms underlying the heteroblastic process by analysing the temporal expression of microRNAs and targets in leaves as well as the leaf metabolome during P. edulis development. Key Results: Metabolic profiling revealed a unique composition of metabolites associated with leaf heteroblasty. Increasing levels of glucose and α-trehalose were observed during juvenile-to-adult phase transition. Accumulation of microRNA156 (miR156) correlated with juvenile leaf traits, whilst miR172 transcript accumulation was associated with leaf adult traits. Importantly, glucose may mediate adult leaf characteristics during de novo shoot organogenesis by modulating miR156-targeted PeSPL9 expression levels at early stages of shoot development. Conclusions: Altogether, our results suggest that specific sugars may act as co-regulators, along with two microRNAs, leading to leaf morphological modifications throughout juvenile-to-adult phase transition in P. edulis.
Keywords: de novo shoot organogenesis; Heteroblasty; microRNA; Passiflora edulis; sugar